Current Accessibility Challenges to Dental Care - A. K. Avetisyan; R. S. Tsyganok (Здоровье мегаполиса, 2024)
Introduction. Access to dental care is a key aspect of ensuring public health and well-being. Modern healthcare systems face many challenges related to the provision of high-quality dental services to all patients seeking for medical help. There is a wide range of challenges, from financial and organizational issues to social and cultural aspects. Lack of dental care affects not only oral health but health in general. Limited access to dental care can lead to tooth decay or other conditions that require expensive treatment in hospital settings, thus disrupting more urgent medical needs.The purpose of this work was to consider the current problems related to the accessibility of dental care. To this purpose, an analysis of Russian and foreign scientific literature was carried out.Materials and methods. This study used general scientific research methods (generalization, analysis, and synthesis). Papers by Russian and foreign authors as well as analytical reports on public and private programs that contribute to increasing the availability of dental medical care were studied.Results. In the context of universal health care, access to dental care is considered a vital public health issue. Financial, geographical, cultural, and social barriers to dental care are considered the most significant. In the Russian Federation, according to the Federal State Statistics Service (Rosstat), about 30% of the population does not have regular access to dental services due to financial and geographical barriers.